A Knowledge Improvement of Adolescent Girls with Weekly Iron Folic Acid Supplementation (Wifas) Education - Susanti, Dwi; Nursanti, Ida; Ekawati (MEDIA ILMU KESEHATAN, 2025)
Background: Adolescent girls' compliance in consuming blood supplement tablets is still low. The results of previous studies show that the compliance of adolescent girls in consuming blood supplement tablets is influenced by knowledge, parental support, teacher support, peer support and self-efficacy. Increasing the knowledge of adolescent girls in consuming blood supplement tablets be given education on how to consume blood supplement tablets, namely with Weekly Iron-Folic Acid Supplementation (WIFAS).Objective: To determine the effectiveness of Weekly Iron-Folic Acid Supplementation (WIFAS) Education on increasing the knowledge of adolescent girls.Methods: This research was conducted at SMA N 1 Godean with a sample size of 84 students. The sampling technique used was purposive sampling. Pretest was done before giving education using video, while pretest was done 1 month after education. Data analysis used univariate analysis and for bivariate analysis using the Wilcoxon testResults: The level of knowledge of adolescent girls before education is mostly in the moderate category, namely 40.1%, and has increased after education in the good category, namely 83.3%. The Wilcoxon test results showed a p-value of 0,01.Conclusion: Weekly Iron-Folic Acid Supplementation (WIFAS) education is effective in improving the knowledge of adolescent girls